Reatando os nós: arte & fato galeria, museu de arte contemporânea do Rio Grande do Sul- MAC/RS e Torreão espaços de legitimação em Porto Alegre (1985-1997) - Machado, Ana Méri Zavadil (2011)
This research aims investigate three spaces of exhibitions, where each one guards its specificity: The Art & Fact Gallery, a commercial space; the Contemporary Art Museum of Rio Grande do Sul MACS/RS, a institutional space and the Torreão, a collective initiative of artists, in a meaningful time covering the years of 1985 and 1997, in Porto Alegre City. What interested us searching, mainly, was the feature common on all three, that is, the extent to which each contributed as a space of legitimation of artists who were beginning their careers in the mid 80's and 90's. From the historiography did the analysis of the performances of such spaces in relation to production, distribution and consumption of art in that period, despite the relationships between spaces, the artists and arts system in force, noting the changes that promoted into the field of art in Porto Alegre. The survey, regarding the methodology, procedures relating to research combines theoretical and field. The first will have its foundation in important authors who wrote about the period as Iclaia Cattani, Blanca Brites, Marilene Burtet Pieta, Anna Maria Albani de Carvalho and Maria Amelia Bulhões, like Gomes and Paulo Tadeu Chiarelli, and other influential theorists different areas such as Anne Cauquelin, Nathalie Heinich, Pierre Bourdieu, Sonia Saltztein, Ricardo Basbaum and Ligia Canongia. To reach our goals the field research was fundamental because the interviews with officials, directors and managers, was instructive, because understanding its dynamic presentation of art, we understand them as spaces of legitimation.